Effect of International Trade on the Economic Growth of Nepal - Acharya, Maya (Janabhawana Research Journal, 2024)
The study explores the relationship between exports, imports, remittance, and economic growth of Nepal for the 1974/75 to 2021/22 fiscal year. Descriptive and analytical research designs were employed on time series data obtained from secondary sources. The Augmented Dickey-Fuller unit root test, co-integration technique, and Error Correction Model (ECM) were employed for empirical investigation. The impact of exports, imports, and remittances on economic growth was analyzed through the ordinary least square regression method for the long run relationship. The result reveals the existence of a long-run relationship between imports, remittances, and gross domestic product. The effect of exports and imports was statistically significant on the economic growth of Nepal and the effects of remittance was statistically insignificant on economic growth. The result emphasizes that the Government should ensure the export promotion policies to achieve Nepal's high and sustainable economic growth by investing in trade infrastructure and export subsidies and creating a favorable environment that encourages using remittance money to support productive sectors of the economy.